Use of AHP Method in Cooperative Information System KJKS BMT Cangkeh Padang Village in the Provision of Medium and Lower Venture Capital Assistance - Ali Akbar Ritonga; Budianto Bangun; Iwan Purnama; Ibnu Rasyid Munthe; Windo (Institute of Computer Science (IOCS), 2020)
Final entitled